2018
DOI: 10.1002/adma.201801021
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrabroadband Mid‐Infrared Pulsed Optical Switch Employing Solution‐Processed Bismuth Oxyselenide

Abstract: Pulsed lasers operating in the mid-infrared (3-25 µm) are increasingly becoming the light source of choice for a wide range of industrial and scientific applications such as spectroscopy, biomedical research, sensing, imaging, and communication. Up to now, one of the factors limiting the mid-infrared pulsed lasers is the lack of optical switch with a capability of pulse generation, especially for those with wideband response. Here, a semiconductor material of bismuth oxyselenide (Bi O Se) with a facile process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 58 publications
2
92
0
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34][35][36] Due to the different parameters of the passively mode-locked fiber laser cavity, different soliton outputs can be achieved, such as traditional soliton, noise-like soliton, bound state soliton, dissipative soliton, multipulse operation, etc. [37][38][39][40][41][42][43][44] Among them, only multi-pulse operation can effectively improve the RPR of mode-locking pulse without reducing the cavity length. Harmonic mode locking is a special multi-pulse operation.…”
Section: Doi: 101002/smll201902811mentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36] Due to the different parameters of the passively mode-locked fiber laser cavity, different soliton outputs can be achieved, such as traditional soliton, noise-like soliton, bound state soliton, dissipative soliton, multipulse operation, etc. [37][38][39][40][41][42][43][44] Among them, only multi-pulse operation can effectively improve the RPR of mode-locking pulse without reducing the cavity length. Harmonic mode locking is a special multi-pulse operation.…”
Section: Doi: 101002/smll201902811mentioning
confidence: 99%
“…Liu's group reported utrasensitive Bi 2 O 2 Se phototransistors with a responsivity up to 3.5 × 10 4 A · W −1 at 532 nm, while the dark current was just several pA [169]. Tian et al focused on nonlinear absorption of polycrystalline Bi 2 O 2 Se, demonstrating an ultrabroadband optical switch covering the NIR and mid-infrared ray ranges [178]. Yin et al reported an infrared PD based on 2D Bi 2 O 2 Se, which demonstrated a high sensitivity of 65 A · W −1 at 1200 nm and ultrafast photoresponse of ~1 ps at room temperature ( Figure 6J) [171].…”
Section: Bi 2 O 2 Sementioning
confidence: 99%
“…Mid‐IR light source is crucial for various applications related to spectroscopy, sensing, and imaging in the molecular fingerprint region . Design and fabrication of new luminescent materials operating in the Mid‐IR region lies in the core of this topic .…”
Section: Introductionmentioning
confidence: 99%
“…Mid-IR light source is crucial for various applications related to spectroscopy, sensing, and imaging in the molecular fingerprint region. [1][2][3][4][5][6][7][8] Design and fabrication of new luminescent materials operating in the Mid-IR region lies in the core of this topic. [9][10][11][12][13] In order to obtain materials with broadband emission, many approaches such as codoped with rare-earth ions, embedding Mid-IR activators into chalcogenide glasses, etc., have been explored.…”
Section: Introductionmentioning
confidence: 99%